IMPLEMENTASI STRATEGI PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING (CTL) DAN CONCEPT MAPPING BERBASIS MULTIPLE INTELLIGENCE TERHADAP PRESTASI BELAJAR AKUNTANSI MAHASISWA PROGRAM STUDI PENDIDIKAN EKONOMI STKIP HAMZANWADI SELONG LOMBOK TIMUR - zein, rohaeniah (Universitas Hamzanwadi, 2015)
The student learning achievement was still low, it can be seen from more than >50% of student number not achieving the Minimum Passing Criteria (KKM) for daily quiz value Basic of Accounting II. It is because of inappropriate learning use. While the Principle Accounting II in accounting cycle of trading company learning material has aplicatif and interconnection betwen one concept and another, so that there should be a learning strategy can apply and describe the concept interconnection. This research aimed to find out: (1) differences in learning achievement of accounting student who use the Contextual Teaching and Learning and Concept Mapping instructional strategy, (2) differences in learning achievement of accounting student who had high category and low category of multiple intelligence, (3) interaction effect between kategory multiple intelligence, CTL and Concept Mapping. This study was a experiment. The research was desained by faktorial 2x2. The sample was taken by using nonprobability sampling kuota. The data collection was taken by document, questionnaire and test method. The conclusion of this research were that: (1) There were differences in learning achievement of accounting student who used the Contextual Teaching and Learning and Concept Mapping instructional strategy. (2) There were differences in learning achievement of student who had the high category and the low category of multiple intelligence. (3) There was an interaction effect between kategory miltiple intelligences, Contextual Teaching and Learning and Concept Mapping instructional strategy. The everage learning achievement (Basic of Accounting II) of experiment class (CTL) higher than the control class (Concept Mapping), and different category of multiple intelligences to effect different of learning achievement. Key Words: Multiple Intelligences, CTL, Concept Mapping, Learning Achievement.